METHOD FOR NUCLEIC ACID DETECTION (2018)
The object of the present invention is a method for detection of a nucleic acid in a sample by nucleic acid separation and enrichment by using a bidirectional electro-hydrodynamic flow in a non-newtonian liquid medium, where the method further comprises the addition of probes intended to hybridize with a target nucleic acid so as to introduce a modification of the molecular weight of the target nucleic acid during hybridization with the probes in order to allow the separation of nucleic acid/probe complexes from the nucleic acid alone or the probes alone when the sample is subject to hydrodynamic and electrical action in order to allow the detection of the target nucleic acid.